Peningkatan Keaktifan Belajar IPS Melalui Model Pembelajaran Time Token Arends dengan Media Gambar pada Siswa Kelas V SD Muhammadiyah 11 Mangkuyudan Tahun 2015/2016 - Suwartini, Suwartini (2016)
This study aims to determine the increase in students' learning activeness in social studies using the Time Token Arends learning model with media images on a fifth grade students of SD Muhammadiyah 11 Mangkuyudan. This research is a classroom action research with the research design consists of four stages: planning, implementation, observation and reflection. His research is class V SD Muhammadiyah 11 Mangkuyudan. Data collection techniques by observation, interviews, documentation and testing. Data analysis technique used is the reduction, data presentation and draw conclusions. The results showed an increase in activity and learning outcomes of students of class V SD Muhammadiyah 11 Mangkuyudan. Increased activity of Learning students as follows: in the first cycle mengajukkan question 26 students or 68.42%, answered questions of 25 students or 65.79%, of expression of 23 students or 60.53%, and completed 29 students or 76.32%, while in the second cycle mengajukkan question 34 students or 89.47%, answered questions of 32 students or 84.21%, of expression of 33 students or 86.84%, and completed 34 students or 89.47%. Students who KKM in the first cycle of 25 students or 65.79% and cycle II 32 students or 84.21%. From this study it can be concluded through the application of learning models Time Token Arends with media images can enhance the activity of students of class V SD Muhammadiyah 11 Mangkuyudan year 2015/2016.